The Most Beautiful Place on Earth : Wallace Stegner in California - Stewart, Matthew D, 1982- (Book collections on Project MUSE., 2022)
"Wallace Stegner is widely regarded as the preeminent twentieth-century writer of the American West. Often referred to as the "Dean of Western Writers" (a title which he didn't care for), Stegner enjoyed a successful and prolific career, working at Stanford University and winning the Pulitzer Prize for Fiction in 1972 for his novel Angle of Repose. In this manuscript, Matthew Stewart explores Stegner's fiction, essays, as well as the countless letters he received from fans and fellow intellectuals, to as Stewart puts it, "defend, clarify, and mourn" Stegner's "geography of hope." Stewart's study is as much about place as it is about Stegner, as it takes up what it means to be part of communities like southern California or the American West, and how Stegner's connections to and ideas about these places changed over time"--